(untitled) (Cardiovascular Journal, 2012)
Background: Infectious diseases are among the leading causes of death and sometimes curable. Bacteria are the most common etiology in hospitalized patients. The objective of this study was to evaluate the incidence of bacterial infections and their pattern of susceptibility to antibiotics in moderate and severe infections in patients admitted at NICVD hospital. Methodology: The study was performed in the apical teaching hospital of Bangladesh situated at Dhaka in the first half of 2012. Patients admitted in medical wards and medical ICU, suffering from moderate and severe infections were studied. Clinical evaluation, routine and specific investigations were done in each case. Microbiological samplings were tried on day 1, after completion of antibiotic therapy or in between as required. Aerobic bacterial culture and sensitivity tests were done. Result: A total of 274 cases were studied of which male (67.5%) were predominant than female (32.5%). The highest number of patients were in the age group of 30-60 years (53.6%) followed by 10- 30 years (24.5%) and more than 60 years (12.8%). The mean age with standard deviation was 39.15±19.07 years (range 1-90 years). Most common isolated bacteria was the Pseudomonas species (14.2%) followed by Escherichia coli (13.5%), Staphylococcus saprophyticus (6.9%) and Staphylococcus aureus (2.2%). From these specimens Pseudomonas species (31.5%) was isolated mostly from pus. E. coli was found most commonly in pus (16.3%) and urine (14.1%). Staph saprophyticus (13.0%) and Staphylococcus aureus (4.3%) were both found most commonly in pus. Pseudomonas species was 100% resistant to Penicillin, Amoxycillin and Vancomycin. It was found that Pseudomonas species was still more than 90% sensitive only to Imipenem. Escherichia coli was more than 80% sensitive to only Imipenem and Amikacin. Staphylococcus aureus was sensitive to only Imipenem and Cephalexin. Conclusion: In this study Pseudomonas species and Escherichia coli are the most common isolated bacteria in this Institution. Most of the antibiotics are resistant to these two bacteria. DOI: http://dx.doi.org/10.3329/cardio.v5i1.12276 Cardiovasc. j. 2012; 5(1): 67-72